2020
DOI: 10.1039/c9nr10387b
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial synthesis of ultrathin β-In2Se3/MoS2 heterostructures with high visible/near-infrared photoresponse

Abstract: Novel β-In2Se3/MoS2 vertically stacked heterostructures were synthesized, and can be further utilized as excellent photodetectors in the visible and near-infrared range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…Similar to the TMD–TMD heterostructures, when group III chalcogenides such as GaTe, GaSe, InSe, and In 2 Se 3 are constructed with TMDs, typical type‐II band alignments with the excellent electron–hole pair separation ability are usually formed. [ 46–49 ] For group IV chalcogenides such as SnS 2 and SnSe 2 , band‐to‐band tunneling phenomena can be observed by applying various biases in a broken‐gap heterojunction. [ 50,51 ] In addition, due to the appropriate direct bandgap, large absorption coefficient, long carrier diffusion length, and high charge carrier mobility of perovskites, the heterostructures built by 2D TMDs and perovskite are found to exhibit significantly improved light absorption and carrier transport efficiency.…”
Section: Types Of Band Structures In 2d Tmd Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the TMD–TMD heterostructures, when group III chalcogenides such as GaTe, GaSe, InSe, and In 2 Se 3 are constructed with TMDs, typical type‐II band alignments with the excellent electron–hole pair separation ability are usually formed. [ 46–49 ] For group IV chalcogenides such as SnS 2 and SnSe 2 , band‐to‐band tunneling phenomena can be observed by applying various biases in a broken‐gap heterojunction. [ 50,51 ] In addition, due to the appropriate direct bandgap, large absorption coefficient, long carrier diffusion length, and high charge carrier mobility of perovskites, the heterostructures built by 2D TMDs and perovskite are found to exhibit significantly improved light absorption and carrier transport efficiency.…”
Section: Types Of Band Structures In 2d Tmd Heterostructuresmentioning
confidence: 99%
“…[ 131 ] Zou et al reported the controlled growth of vertically stacked β ‐In 2 Se 3 /MoS 2 vdW heterostructures through a typical two‐step CVD method. [ 49 ] Both the conduction band minimum and the valence band maximum of In 2 Se 3 are lower than those of MoS 2 , leading to a type‐II band alignment between the two components. Under 532 nm light, electron–hole pairs will be generated in both In 2 Se 3 and MoS 2 .…”
Section: Band Alignment Strategies and Mechanism In Photodetectorsmentioning
confidence: 99%
“…Another important function of heterostructure is to expand the working wavelength of the device. As WSe 2 /Bi 2 Te 3 p–n heterostructure, [ 14 ] β‐In 2 Se 3 /MoS 2 heterostructures, [ 15 ] and H‐MoTe 2 /MoS 2 heterostructure, [ 16 ] they all widen their photodetection range from visible to near‐infrared region. Graphene, as a semimetal, can expand the working wavelength of MoS 2 ‐based photodetectors to IR range because of the broad band characteristics, which comes from its zero bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…The photocurrent could stabilize from 100 to 500 pA under various light intensities with the rise and fall time of 20 and 24 ms shown in Fig. 2 e, f. This device demonstrated a faster light response than most of the In 2 Se 3 based photodetectors developed by other groups [ 18 , 37 40 ]. Recent theoretical calculation predicts that the photocurrent generation from a α-In 2 Se 3 /3R MoS 2 heterojunction could cover from visible light to near infrared region, with a higher optical absorption coefficient and current density than an isolated In 2 Se 3 layer [ 27 ].…”
Section: Resultsmentioning
confidence: 70%
“…Recent theoretical calculation predicts that the photocurrent generation from a α-In 2 Se 3 /3R MoS 2 heterojunction could cover from visible light to near infrared region, with a higher optical absorption coefficient and current density than an isolated In 2 Se 3 layer [ 27 ]. Indeed, infrared photoresponse from few layer β-In 2 Se 3 /monolayer MoS 2 heterojunctions showed an extended detection range from the visible to near infrared region [ 37 ], due to the relatively small bandgap of β-In 2 Se 3 . As few layer β-In 2 Se 3 and monolayer MoS 2 were involved, the light absorption of their devices could not be high.…”
Section: Resultsmentioning
confidence: 99%